2017
DOI: 10.1016/j.cej.2017.03.056
|View full text |Cite
|
Sign up to set email alerts
|

Activation process of air stable nanoscale zero-valent iron particles

Abstract: Nanoscale Zero Valent Iron (nZVI) represents a promising material for subsurface water remediation technology. However, dry, bare nZVI particles are highly reactive, being pyrophoric when they are in contact with air. The current trends of nZVI manufacturing lead to the surface passivation of dry nZVI particles with a thin oxide layer, which entails a decrease in their reactivity. In this work an activation procedure to recover the reactivity of air-stable nZVI particles is presented. The method consists of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 47 publications
1
32
0
6
Order By: Relevance
“…Ribas (2017) reported that dry, bare NZVI particles are highly reactive and are pyrophoric when in contact with air. Current trends in NZVI manufacturing lead to surface passivation of dry NZVI particles with a thin oxide layer, resulting in a decrease in their reactivity 35 . The addition of carriers such as powdered activated carbon to NZVI to produce NZVI/GAC reduces the decrease in surface energy and reactivity of NZVI and increases the yield.…”
Section: Resultsmentioning
confidence: 99%
“…Ribas (2017) reported that dry, bare NZVI particles are highly reactive and are pyrophoric when in contact with air. Current trends in NZVI manufacturing lead to surface passivation of dry NZVI particles with a thin oxide layer, resulting in a decrease in their reactivity 35 . The addition of carriers such as powdered activated carbon to NZVI to produce NZVI/GAC reduces the decrease in surface energy and reactivity of NZVI and increases the yield.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, these reports co-exist in the literature with publications demonstrating that Fe 0 surface is universally covered by oxide layers [61][62][63][64][65][66], and that Fe 0 is additionally passivated with corrosion products during the remediation process [44,52,61,67,68]. Numerous recent studies, aimed to gain insight into the principles governing the removal of Cr VI in Fe 0 /H 2 O systems, have also presumed that this process is exclusively the result of direct electron transfer from Fe 0 to Cr VI [69][70][71][72][73][74][75][76][77][78][79]. Since the surface of commercially Fe 0 materials is permanently covered by an outer layer of low electric conductive air-formed oxides (hematite, maghemite) [64], the electron transport from Fe 0 to Cr VI should be severely inhibited [69][70][71][72][73][74][75][76][77][78][79].…”
Section: More Recent Laboratory-scale Reports (Post Elisabeth City Prb)mentioning
confidence: 99%
“…Numerous recent studies, aimed to gain insight into the principles governing the removal of Cr VI in Fe 0 /H 2 O systems, have also presumed that this process is exclusively the result of direct electron transfer from Fe 0 to Cr VI [69][70][71][72][73][74][75][76][77][78][79]. Since the surface of commercially Fe 0 materials is permanently covered by an outer layer of low electric conductive air-formed oxides (hematite, maghemite) [64], the electron transport from Fe 0 to Cr VI should be severely inhibited [69][70][71][72][73][74][75][76][77][78][79]. Moreover, Fe 0 efficiency should significantly decrease during the time, as its surface is progressively covered with additional secondary mineral coatings that prevents penetration of the Cr VI and stops the electron transfer [11,[80][81][82].…”
Section: More Recent Laboratory-scale Reports (Post Elisabeth City Prb)mentioning
confidence: 99%
“…Initially, to prepare the nZVI slurry, 250 g of nZVI particles were mixed to 1000 mL of deionized water to check the slurry's consistency. After this, the preparation was done to fill a 5000 mL container at a final w/w Fe to water ratio of 0.25 [27]. The Fe 0 content in the slurry was measured to be 93%, based on the amount of hydrogen gas emitted when iron nanoparticles react at a volumetric volume of 60% with the addition of sulfuric acid [28].…”
Section: Materials and Initial Experimentsmentioning
confidence: 99%